Sexual practices, contraception and voluntary abortion among women of the working class es in Salvador - Sardenberg, Cecilia M. B. (FCL-UNESP Laboratório Editorial, 2012)
In this article, we reflect upon sexual practices, contraception and voluntary abortion among low-income women from Salvador based on the results of a survey conducted to identify and analyze processes of women’s empowerment. This involves making strategic decisions and, as such, taking greater control over their bodies and lives. While following this notion of empowerment, we sought to learn how (353) women of different generations residing in Plataforma, in the outskirts of the city, identify and have made use of the resources and conditions at hand to make strategic choices. In this discussion, we limit ourselves to analyzing quantitative data on women’s sexual and reproductive lives by focusing on: a) age at first sexual relation; b) number of partners; c) importance of sex and orgasm to women; d) habit of masturbation; e) safe sex; f) contraceptive methods; and g) voluntary abortion.